Retrospective analysis of ribociclib and letrozole as first-line therapy in patients with hormone receptor (HR) positive metastatic breast cancer (MBC) within a managed access program (MAP) in Turkey. - Basaran, Gul; Demirci, Umut; Yildiz, Fatih; Cicin, Irfan; Aktas, Burak Yasin; Ozturk, Banu; Goksu, Sema Sezgin; Coskun, Hasan Senol; Oyan, Basak; Sonmez, Ozlem; Eralp, Yesim; Gokmen, Erhan; et al. (LIPPINCOTT WILLIAMS \& WILKINS, 2020)
Annual Meeting of the American-Society-of-Clinical-Oncology (ASCO), ELECTR NETWORK, MAY 29-31, 2020